Śrīśrīyugācāryya saṅga o upadeśāmrta : jāti-saṃgaṭhaka o dharmma-saṃthāpaka Ācāryya Śrīmaṯ Svāmī Praṇabānandajī Mahārājera saṅga o upadeśābalī - Ātmānanda, Swami (Praṇaba Maṭha : prāptira sthāna, Bhārata Sebāśrama Saṅgha, 1977)
Author's impression about Swami Pranavananda, 1896-1941, founder of the Hindu socioreligious organization Bharat Sevasram Sangha; includes selected discourses.